On local cohomology and local homology based on an arbitrary support - Sarria, Luis Alberto Alba (2015)
This work develops the theories of local cohomology and local homology with respect to an arbitrary set of ideals and generalises most of the important results from the classical theories. It also introduces the category of quasi-holonomic D-modules and proves some finiteness properties of local cohomology modules which generalise Lyubeznik's results in some sense.